Interfacial stress distribution analysis of natural fiberreinforced epoxy composites: a finite element approach - Ikramullah, Ikramullah; Gapatra, Reja; Ananda, Seprian Haris; Kurniawan, Rudi; Fonna, Syarizal; Rizal, Samsul; Huzni, Syifaul (Jurnal Polimesin, 2024)
The strength of fiber-reinforced composites is greatly influenced by the bonding at the fiber-matrix interface. Experimental methods to study this interface are often challenging, making numerical approaches essential for evaluating the interfacial behavior in fiber-reinforced composites. This study investigates the stress and strain distribution in the fiber, matrix, and fibermatrix interface regions of natural fiber-reinforced single-fiber composites under tensile loading using the finite element method. Interface conditions were modeled using cohesive elements, with the composites represented in two dimensions through ABAQUS 6.14 software. The tie constrains contact model was employed to define binding interactions between the cohesive element, the fiber, and the matrix. The maximum stress value resulting from the simulation process is 202 MPa and a strain of 0.0449 mm. The stress is effectively distributed to the fiber, demonstrating that the cohesive element used in composite analysis under tensile loading serves as a reliable link between the fiber and the matrix. The simulation results revealed a maximum stress value of 202 MPa and a corresponding strain of 0.0449 mm. The stress distribution effectively transferred to the fiber, demonstrating the capability of cohesive elements to represent the interfacial bond in composites under tensile loading. These findings confirm that cohesive element modeling is reliable method for analyzing fibermatrix interactions in natural fiber reinforced composites, providing insights for optimizing composite performance.